MANAJEMEN STRATEGI DIVISI KEWIRAUSAHAAN UNESA CAREER CENTER (UCC) DALAM MENINGKATKAN MINAT KEWIRAUSAHAAN MAHASISWA UNIVERSITAS NEGERI SURABAYA - Meirinawati Meirinawati; Muhammad Fariz Zarvan (Universitas Negeri Surabaya, 2022)
The Ministry of Education and Culture issued Decree No. 3/M/2021 on Key Performance Indicators (KPI), the decision was issued for the reason of seeing the increasingly difficult labor conditions in Indonesia. Thus, it is expected to increase the role of students in the field of entrepreneurship so as to create new jobs. The State University of Surabaya as one of the collague in Indonesia answer this challenge by establishing the Unesa Career Center (UCC) as a special institution in preparing students and alumni to be able to compete in the business sector. The purpose of this research is to find out about the strategy of UCC's entrepreneurship division in increasing the entrepreneurial interest of its students. This type of research is descriptive qualitative. The focus of research is in terms of seven (7) steps of strategic management theory, Suyanto, 2007. Data were collected through observation, documentation, interview, and literature study. Analysis of the data through data collection, reduction, presentation, and conclude. Result of the research shows that the strategic management that used by the UCC entrepreneurship division has been going quite well. However, the researcher have some suggestions for future improvement, such as: making more detailed goals, equitable distribution of HR competencies, budget management to re-optimizing the external evaluation process from student input. Keywords: Entrepreneurship, Strategic Management, Unesa Career Center